Interfacial interactions and complex segmental dynamics in systems based on silica-polydimethylsiloxane core–shell nanoparticles: Dielectric and thermal study. (10th February 2015) - Klonos, P.; Sulym, I.Ya.; Borysenko, M.V.; Gun'ko, V.M.; Kripotou, S.; Kyritsis, A.; Pissis, P.
Abstract: Effects of two types of silica particles, with different characteristics of porosity, on segmental mobility of poly(dimethylsiloxane), PDMS, in core–shell nanocomposites with two contents of polymer, 40 and 80 wt%, were studied by employing thermal (DSC) and dielectric (DRS, TSDC) techniques, under different annealing procedures. Filler morphology and polymer–particle interactions were found to affect PDMS crystallinity and segmental mobility. The dielectric techniques allowed the detection of four contributions to the segmental dynamics associated with the glass transition arising, in the order of decreasing mobility, from confined polymer chains in the pores of silica gel ( α p relaxation), from the bulk (unaffected) amorphous polymer fraction ( α relaxation), from polymer chains restricted between condensed crystal regions ( α c ) and from semibound polymer in an interfacial layer close to the nanoparticle surface ( α′ ). For the core–shell nanocomposites with high PDMS content (80 wt%) the interfacial α′ relaxation process is found to have similar characteristics with that in conventional PDMS/silica nanocomposites, for lower PDMS content (40 wt%), however, the interfacial relaxation process exhibits distinct differences. The experimental findings are discussed in terms of models proposed for the description of conformations of polymers adsorbed onto a solid surface. Graphical abstract: Highlights: Strong interactions in silica-PDMS core–shell systems suppress crystallization. DRS allowed the detection of four contributions to segmental dynamics. Interfacial dynamics dominates segmental mobility for low polymer content. Interfacial dynamics is strongly suppressed after crystallization annealing. Models involving bimodal conformations can describe well the interfacial mobility.